2013
DOI: 10.1097/mcg.0b013e3182688c15
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Metabolic Syndrome and Colorectal Neoplasm

Abstract: Background There has been constant speculation about the association between metabolic syndrome (MetS) and colorectal neoplasia (CN); however, the published results are conflicting. The aims of this study are to systematic search, and assess literature to determine the available evidence on the association between these two conditions. Methods Meta-analysis was conducted based on relevant studies identified through a systematic literature review from PubMed, OvidSP and Cochrane database during January 1980 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 43 publications
(39 reference statements)
5
58
1
3
Order By: Relevance
“…[2][3][4][5] MetS is also shown to be associated with an increased risk of colorectal cancer incidence and mortality in both sexes. 6,7 We also have shown that increasing the area of visceral fat assessed with computed tomography (CT) scans and a decreased concentration of plasma adiponectin are associated with the development of colorectal cancer and also adenoma, which is its precursor lesion. 8,9 Hyperinsulinaemia due to insulin resistance and its influence in enhancing free or bioavailable concentrations of insulin-like growth factor-1, and altered levels of adipokines and their contribution to chronic low-grade inflammation are suggested to play a pivotal role in increasing colorectal cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] MetS is also shown to be associated with an increased risk of colorectal cancer incidence and mortality in both sexes. 6,7 We also have shown that increasing the area of visceral fat assessed with computed tomography (CT) scans and a decreased concentration of plasma adiponectin are associated with the development of colorectal cancer and also adenoma, which is its precursor lesion. 8,9 Hyperinsulinaemia due to insulin resistance and its influence in enhancing free or bioavailable concentrations of insulin-like growth factor-1, and altered levels of adipokines and their contribution to chronic low-grade inflammation are suggested to play a pivotal role in increasing colorectal cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты метаанализов подтверждают ассоци-ацию наличия МС с повышенным риском развития КРР [28,29,30] ; ≥3 критериев против <3 критериев), значимость связи нивелировалась в мультивариантной модели. В данном исследовании также не обнаружили связи МС с КРР как у мужчин, так и у женщин (RR=1,34; 95% CI: 0,9-2,0 и RR=1,34; 95% CI: 0,9-2,1 соответ-ственно) [11].…”
Section: результатыunclassified
“…dokonali analizy badań zamieszczonych w bazie Pub Med, OvidSP i Cochrane w latach 1980-2011. Oszacowali, że zespół metaboliczny wiązał się z istotnie wyższym ryzykiem zachorowania na raka jelita grubego [7]. Klimczak i wsp.…”
Section: Dyskusjaunclassified